PENINGKATAN KUALITAS PRODUK UMKM MELALUI DIGITAL MARKETING DAN LEGALITAS PRODUK DI DESA CERME - Ulum, Achmad Saiful; Theressa, Thea Diva; Firmansyah, Ade; Rohman, Fathur (Jurnal Terapan Abdimas, 2023)
Abstract. The Covid-19 pandemic has hit Indonesia, so it has had a lot of impact on the community's economy, especially MSME actors. The impact is a decrease in sales turnover, a decrease in product sales, and difficulties in financing loan installments. Around 47, 13% of businesses were able to survive in August 2020, around 72.02% of businesses would close in November 2020, and around 85.42% could last a maximum of one year during the Covid-19 Pandemic era. The impact of the Covid-19 pandemic was also felt by Micro MSME actors in Cerme Village, Nganjuk Regency who are partners in this community service program. The number of MSMEs in Cerme Village is 15 Micro Business actors. The types of businesses that are run are Food, Beverage, Natural Stone, Bonsai, and Plantation. The purpose of this community service program is to help MSME actors, especially in Cerme Village, Nganjuk Regency in overcoming the problem of decreasing sales turnover in the Covid-19 pandemic era. The implementation method for this community service activity is carried out in a Hybrid manner, namely a combination of offline and online. Meanwhile, this community service method consists of 3 stages, namely the metric exposure method, practice and mentoring. The results of community service that have been carried out include: Increased knowledge of MSMEs, especially in Cerme Village in mapping marketing strategies and Digital Marketing, Being able to determine the Promotional Mix, and product packaging, Increasing public knowledge in the use of marketing technology that aims to expand product marketing, Increasing public interest in legalizing this type of business.Abstrak. Pandemi Covid-19 telah melanda di Indonesia, sehingga banyak menimbulkan dampak pada ekonomi masyarakat khususnya pelaku UMKM. Dampak yang ditimbulkan yaitu penuruann omset penjualan, menurunnya penjualan produk, dan kesulitan dalam membiayai angsuran pinjaman. Sekitar 47, 13% usaha mampu bertahan di Bulan Agustsus 2020, sekitar 72,02% usaha akan tutup di Bulan November 2020, dan sekitar 85,42% dapat bertahan paling lama satu tahun pada era Pandemi Covid-19. Dampak pandemi Covid-19 juga dirasakan oleh Pelaku UMKM Mikro di Desa Cerme, Kabupaten Nganjuk yang merupakan Mitra dalam program pengabdian Masyarakat ini. Jumlah UMKM yang berada di Desa Cerme sebanyak 15 pelaku Usaha Mikro. Jenis usaha yang dijalankan yaitu Makanan, Minuman, Batu Alam, Bonsai, dan Perkebunan. Tujuan Program pengabdian masysrakat ini yaitu untuk membantu para pelaku UMKM khususnya di Desa Cerme Kabupaten Nganjuk dalam mengatasi permasalahan penurunan omset penjualan di era pandemic Covid-19. Metode pelaksanaan pada kegiatan Pengabdian masyarakat ini dilaksanakan secara Hybrid yaitu kombinasi antara Luring dan daring. Sedangkan metode pengabdian Masyarakat ini terdiri dari 3 Tahapan yaitu Metode Pemaparan metri, Praktika dan Pendampingan. Adapun hasil dari pengabdian masyarakat yang telah dilakukan diantaranya yaitu : Meningkatnya pengetahuan UMKM khususnya di Desa Cerme dalam memetakan strategi pemasaran dan Digital Marketing, Mampu menentukan Bauran Promosi, dan kemasan produk, Meningkatnya pengetahuan masyarakan dalam pemanfaatan teknologi pemasaran yang bertujuan untuk memperluas pemasaran produk, Meningkatnya minat masyarakat dalam melegalitaskan jenis usahanya.